Tapping slag from experimental blast furnace (1930)
Three views of Mr. Royster (left) and Travis Hignett (right) tapping slag from the experimental blast furnace at the U.S. Department of Agriculture's Fixed Nitrogen Research Laboratory located in Washington, D.C. Mr. Royster appears to be recording the process with a hand-held camera. The Fixed Nitrogen Research Laboratory (F.N.R.L.) was established at American University in 1919 under the directorship of Arthur B. Lamb. Initially part of the War Department, the F.N.R.L. was the successor to several wartime initiatives to develop a secure domestic supply of nitrate compounds necessary for the manufacture of explosives during World War I. With a staff of about 110 individuals, including 35 to 50 chemists, the F.N.R.L. focused on the manufacture, production, and development of products of atmospheric nitrogen, including munitions and fertilizers.
Keywords: Employees; Blast furnaces; Nitrogen--Fixation; United States. Bureau of Chemistry and Soils; Furnaces; United States. Department of Agriculture; Nitrogen fertilizer industry